Governing together in good and bad economic times: the fulfilment of election pledges in Ireland. Issue 2 (2nd April 2016) - Thomson, Robert; Costello, Rory
ABSTRACT: The idea that parties make promises to voters during election campaigns and then attempt to fulfil those promises if elected to government is central to the theory and practice of democracy. This study examines how economic conditions affect the fulfilment of parties' election pledges in Ireland. We formulate and test propositions relating to two aspects of economic conditions that negatively affect the likelihood of pledge fulfilment. The first is that parties do not adjust pledges to prevailing economic conditions, and the second is that they do not accurately anticipate future economic conditions. We test these expectations with evidence on the fulfilment of 3681 pledges made by Irish parties in the period 1977–2011, which is one of the largest country-specific datasets on pledge fulfilment currently available. Given the considerable variation in economic conditions faced by Irish governments in this time period, these cases offer a particularly powerful test of the impact of economic conditions on pledge fulfilment.